Individual approach for treatment of primary intestinal lymphangiectasia in children: single-center experience and review of the literature - Kwon, Yiyoung (BMC Pediatr, 2021)
BACKGROUND: Intestinal lymphangiectasia is a rare disease. Thus, prospective studies are impossible, and therapy is still controversial. Several medicines are suggested for treatment but there are no existing indications for drug choice and treatment guidelines. We aimed to introduce the action mechanism of each drug and treatment overview in a single-center experience and a review of the literature on second-line therapy for primary intestinal lymphangiectasia. METHOD: Children under 18 years old diagnosed with intestinal lymphangiectasia from June 2000 to June 2020 were included and retrospectively reviewed in the study. Capsule endoscopy, MR lymphangiography, or whole-body MRI for investigating the extent of abnormal lymphatic vessels in addition to endoscopy and biopsy were conducted. The individual treatment approaches depended upon the lymphangiectasis locations involved. RESULTS: Only one patient showed a response to dietary therapy. One patient was successfully cured after two therapeutic lymphatic embolization. Octreotide was tried for two patients who had extensive lymphangiectasis. Lymphangiectasis recurred when octreotide was used for 3 months in one patient, and there was no effect in the other patient. Sirolimus was tried for four patients. Two of them had abnormal lymphatic lesions only in the intestine, and the others had extensive lymphangiectasis. The former group showed clinical improvement after 3–4 months of sirolimus treatment, whereas the latter group showed clinical improvement only after 1 month of sirolimus treatment. CONCLUSION: Surgery or embolization is a potential therapeutic option for patients with focal abnormal lymphatic lesions. Octreotide is not an optimal choice for patients with extensive lymphangiectasis. Sirolimus is an effective and safe drug and can be the first drug of choice for patients with extensive lymphangiectasis.